Nonylphenol biodegradation characterizations and bacterial composition analysis of an effective consortium NP-M2. (January 2017) - Bai, Naling; Abuduaini, Rexiding; Wang, Sheng; Zhang, Meinan; Zhu, Xufen; Zhao, Yuhua
Abstract: Nonylphenol (NP), ubiquitously detected as the degradation product of nonionic surfactants nonylphenol polyethoxylates, has been reported as an endocrine disrupter. However, most pure microorganisms can degrade only limited species of NP with low degradation efficiencies. To establish a microbial consortium that can effectively degrade different forms of NP, in this study, we isolated a facultative microbial consortium NP-M2 and characterized the biodegradation of NP by it. NP-M2 could degrade 75.61% and 89.75% of 1000 mg/L NP within 48 h and 8 days, respectively; an efficiency higher than that of any other consortium or pure microorganism reported so far. The addition of yeast extract promoted the biodegradation more significantly than that of glucose. Moreover, surface-active compounds secreted into the extracellular environment were hypothesized to promote high-efficiency metabolism of NP. The detoxification of NP by this consortium was determined. The degradation pathway was hypothesized to be initiated by oxidization of the benzene ring, followed by step-wise side-chain biodegradation. The bacterial composition of NP-M2 was determined using 16S rDNA library, and the consortium was found to mainly comprise members of the Sphingomonas, Pseudomonas, Alicycliphilus, and Acidovorax genera, with the former two accounting for 86.86% of the consortium. The high degradation efficiency of NP-M2 indicated that it could be a promising candidate for NP bioremediation in situ. Graphical abstract: Highlights: Consortium NP-M2 could degrade and detoxify nonylphenol effectively. The addition of organic matter promoted biodegradation. Secreted surface-active compounds might facilitate biodegradation. The degradation pathway for NP by NP-M2 was proposed. Bacterial composition was analyzed using the 16S rDNA library. Abstract : Isolation and characterization analysis of an efficient nonylphenol-degrading bacterial consortium with an efficiency higher than that of other reported microorganisms.